Technique of subliminal verbal suggestion for treatment soldiers with PTSD - Chugunov, V. V.; Kurilo, V. A.; Danilevska, N. V; Чугунов, В. В.; Курило, В. А.; Данилевская, Н. В.; Чугунов, Вадим Віталійович; Курило, Віталій Олексійович; Данілевська, Наталя Володимирівна (My University, 2016)
The work is devoted to study the therapeutic viability of psychotherapeutic techniques subliminal verbal suggestion in the treatment of PTSD. The paper considers the factors that may negatively affect compliance to therapy in patients with PTSD. The technique of subliminal verbal suggestion aimed at mitigating these factors and allow without triggering a flashback to eliminate painful traumatic experiences in patients with PTSD. Studied the therapeutic efficacy of this technique. Работа посвящена изучению терапевтической состоятельности психотерапевтической методики подпорогового вербального внушения в терапии ПТСР. В работе рассмотрены факторы, нарушающие комплаенс к терапии у больных ПТСР. Пред¬ложена методика подпорогового вербального внушения, направленная на нивелирование данных факторов и позволяющая без провоцирования флешбеков ликвидировать болезненные психотравмирующие переживания у больных ПТСР. Изучена терапевтическая эффективность данной методики.
Методика подпорогового вербального внушения для терапии военнослужащих с ПТСР
Keywords: subliminal verbal suggestion; PTSD; psychotherapy; подпороговое вербальное внушение; ПТСР; психотерапия